Awareness about Sickle Cell Disease among the Female Students in KAU-Rabigh, Saudi Arabia, 2020, A Cross Sectional Study (Indian Journal of Public Health Research & Development, 2023)
Background: In Saudi Arabia, Sickle cell disease (SCD) is a relatively common inherited disorder. In spiteofobligatorypremarital genetic counseling, no significant changes in SCD prevalence over the last 15 years.Awareness regarding SCD is a way in trying of controlling and modify the problem. The aimis to assess the levelof awareness about people living with SCD among undergraduate female Students at King Abdulaziz University,Rabigh Branch.Methods: A total of 351 female students were included in our cross-sectional study. Data were collected by aself-administered questionnaire.Results: Good awareness regarding SCD was detected only in 26.78% of the participants. Association betweenawareness and socioeconomic data detected that most of the students with good awareness were unmarried(97.9%), a higher level of awareness was in the medical students (51.1%), and in the higher academic years (59.5%were in fifth and fourth years).Conclusion: There was inadequate awareness of SCD, to reduce the incidence, we suggest effective public healtheducation for sickle cell trait and SCD in strategic places such as schools, media,and health centers to addressmisconceptions and increase knowledge as well as an understanding of the risks of having a child with SCD andinfluence the personal reproductive decision.
Keywords: Sickle cell disease, Inheritance, female Students, Rabigh